Influence of extracellular magnesium ions on the functional state and biophysical and structural properties of connexin36 hemichannels - Aníbal García; Valeria Márquez-Miranda; Nicolás Bravo-Acuña; Ingrid Araya-Duran; Maximiliano Rojas; Nicolás Palacios-Prado; John O’Brien; Fernando D. González-Nilo; Juan C. Sáez (Proceedings of the National Academy of Sciences, 2026)
Connexin36 (Cx36) is highly expressed in inhibitory and excitatory neurons as well as pancreatic β-cells, where it forms gap junction channels that coordinate metabolic and electrical responses. In addition, Cx36 forms hemichannels in pancreatic β-cells, where it may play a critical role in endocrine cell signaling. Despite this, the regulatory mechanisms and biophysical properties of Cx36 HCs remain poorly understood. Using HeLa cells lacking endogenous expression of large-pore channels and transfected with mouse Cx36-EGFP, we evaluated hemichannel activity through dye uptake assays and membrane current recordings. We found that Cx36 hemichannel activity is strongly inhibited by extracellular Mg 2+ , rather than Ca 2+ , in contrast to hemichannels formed by other connexins. Under reduced extracellular Mg 2+ , or under alkaline extracellular pH conditions, Cx36 hemichannels exhibited increased activity and allowed Ca 2+ influx, as detected by ratiometric dye FURA-2. Under low extracellular Mg 2+ conditions, Cx36 hemichannels exhibited increased permeability to small molecules and were blocked by La 3+ and quinine, but not by high glucose concentration. In-silico studies revealed interactions between Mg 2+ and two amino acid residues within a pore constriction (D47–E49), which alter the electrostatic potential of the hemichannel pore. Consistent with these observations, mutation of either amino acid residue to alanine (D47A or E49A) markedly reduced the inhibitory effect of extracellular Mg 2+ . Together, these findings offer critical insights into the regulation of Cx36 hemichannels and suggest that alterations in Mg 2+ homeostasis may have significant consequences for Cx36-mediated signaling.